Supply behaviour in New Zealand's export industries - Tweedie, A. J.; Spencer, G. H.; Reserve Bank of New Zealand (Wellington : Reserve Bank of New Zealand, 1981)
This research paper sets out the results of a recent project designed to estimate a series of supply type equations for a range of export commodities. The model is based on annual data for the period 1960 - 1978 and emphasis is on explaining total production
Bibliography: p. 31.
osc 31/01/2019
Loans
Keywords: Industries; Export marketing; Industries; Supply and demand - mathematical methods; Commercial products - mathematical methods; New Zealand